Synthesis under high pressure: crystal structure and properties of cubic Dy36O11F50[AsO3]12 ∙ H2O - Goerigk, Felix Christian; Locke, Ralf Jules Christian; Schleid, Thomas (Frontiers in Chemistry, 2024)
The multi-anionic compound with the composition Dy36O11F50[AsO3]12 ∙ H2O, which can be described in the non-centrosymmetric cubic space group F4¯3c, already shows an unusually large unit cell with an axis of a = 2587.59(14) pm. Its crystal structure exhibits isolated ψ1-tetrahedral [AsO3]3– anions, but both the coordination numbers and the linking schemes of the Dy3+-centered polyhedra differ significantly from the mostly layered structures described so far in literature. (Dy1)3+ is sevenfold coordinated by oxygen atoms and F− anions, forming a capped trigonal prism [(Dy1)O4.333F2.667]8.333–, and the remaining two cations (Dy2)3+ and (Dy3)3+ both reside in an eightfold coordination of anions. In both cases they form slightly distorted square antiprisms, which have the compositions of [(Dy2)O3.667F4.333]8.667– and [(Dy3)O4.667F3.333]9.667–, respectively. Some of the oxygen atoms are not part of ψ1-[AsO3]3– tetrahedra, but occur as O2– anions and one of these even shares a common crystallographic position with fluoride (F−). It is also worth mentioning that the single crystals were obtained as comparatively large cubes with an edge length of several 100 µm providing very good data with regard to single-crystal X-ray diffraction. To verify the simultaneous presence of oxygen and fluorine, electron-beam microprobe analysis was carried out, and a single-crystal Raman spectrum ruled out the presence of hydroxide anions or protonated [AsO3]3– groups, but proved the interstitial crystal-water molecules, which could not be determined precisely by the crystal-structure refinement.